Wireless Sensor Network for Performance Monitoring of Electrical Machine - Priyanka Ranaware; N.D. Dhoot (Institute of Advanced Engineering and Science, 2015)
This paper proposes a novel industrial wireless sensor network for industrial machine condition monitoring. To avoid unexpected equipment failures and obtain higher accuracy in diagnostic and prognostic for the health condition of a motor, efficient and comprehensive data collecting, monitoring, and control play an important role to improve the system more reliable and effective. A novel wireless data collection for health monitoring system of electric machine based on wireless sensor network is proposed and developed in this paper. The unique characteristics of ZigBee networks such as low power, low cost, and high flexibility make them ideal for this application. The proposed system consists of wireless sensor nodes which are organized into a monitoring network by ZigBee protocols. A base station and wireless nodes have been developed to form a prototype system. Various sensors have the capability to monitor physiological as well as environmental conditions. Therefore proposed system provides a flexible solution that makes our living spaces more intelligent.